Strategies for Local Economic Development Through Tourism: A Case Study of Tana Toraja - Ade Irma Surani Haliq; Robby Robby; Hajaruddin A (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2026)
This study analyzes the role of tourism as a Local Economic Development (LED) strategy in Tana Toraja, South Sulawesi. Using a descriptive qualitative approach, the study utilizes secondary data from the Central Statistics Agency (BPS), local government documents, and recent academic literature on tourism and local development. The analysis reveals that culture- and nature-based tourism in Tana Toraja holds significant potential, as evidenced by the increase in domestic tourist visits, which reached 26,662 people during the 2025 Eid al-Fitr period, with the religious destination Buntu Burake serving as the primary attraction. However, tourism development faces challenges such as accessibility issues, infrastructure limitations, and a lack of innovation among local communities. Although annual programs such as Lovely December and the Toraja International Festival have increased the destination’s exposure, sustainable economic linkages have not yet been optimally achieved. This article concludes that the success of tourism as an instrument of LED depends on strengthening community-based institutions, collaboration among stakeholders, the development of supporting infrastructure, and a consistent global branding strategy.